2010
DOI: 10.1007/s11094-010-0483-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antimicrobial activity of dialkyl-2-aryl-6-hydroxy-6-methyl-4-( p-toluenesulfonylaminoimino) cyclohexane-1,3-dicarboxylates

Abstract: Reaction of dialkyl-2-aryl-6-hydroxy-6-methyl-4-oxocyclohexane-1,3-dicarboxylates with tosylhydrazide proceeds via the alicyclic carbonyl group to give dialkyl-2-aryl-6-hydroxy-6-methyl-4-(p-toluenesulfonylaminoimino)cyclohexane-1,3-dicarboxylates. The antimicrobial activity of the synthesized compounds has been evaluated.It was established previously that b-cycloketols and their derivatives exhibit antimicrobial and anti-inflammatory activity [1,2]. It seemed interesting to study the reaction of dialkyl 2-ary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The methods of further modification of the thus prepared cyclohexanones with mono-or polyfunctional nucleophiles are also well studied [20][21][22][23][24][25][26][27][28]. For instance, it was found that reactions of hydroxylamine [9], hydrazine [23,24], ethylenediamine [27], ethanolamine [8,26,27], ethylene glycol [4], substituted aromatic amines [20,21,25], tosylhydrazide [22] and benzidine [28] with diethyl-4-hydroxy-4-methyl-6-oxo-2-phenylcyclohexane-1,3-dicarboxylate give isoxazole, imidazole and 1,3-dioxolane rings, Schiff base condensation products, etc. Moreover, in some cases the cyclization processes depend on temperature, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The methods of further modification of the thus prepared cyclohexanones with mono-or polyfunctional nucleophiles are also well studied [20][21][22][23][24][25][26][27][28]. For instance, it was found that reactions of hydroxylamine [9], hydrazine [23,24], ethylenediamine [27], ethanolamine [8,26,27], ethylene glycol [4], substituted aromatic amines [20,21,25], tosylhydrazide [22] and benzidine [28] with diethyl-4-hydroxy-4-methyl-6-oxo-2-phenylcyclohexane-1,3-dicarboxylate give isoxazole, imidazole and 1,3-dioxolane rings, Schiff base condensation products, etc. Moreover, in some cases the cyclization processes depend on temperature, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Heterocyclic compounds are an important class and have been found as a crucial structural core in natural and synthetic drugs [12]. In recent years, β-keto esters have displayed a number of important biological properties such as bactericidal, fungicidal, and anti-inflammatory activities [13][14][15]. Antioxidants have gained a lot of importance because of their potential prophylactic and therapeutic activities against many diseases.…”
Section: Introductionmentioning
confidence: 99%